2021
DOI: 10.1039/d1ra02861h
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for the preparation of a nickel selenide and cobalt selenide mixed catalyst to enhance bifunctional oxygen activity for Zn–air batteries

Abstract: The mixture Ni0.85Se/Co0.85Se-NHCS-2 displayed superior electrocatalytic performance to that of Ni0.85Se-NHCS or Co0.85Se-NHCS alone. This provided a simple approach to develop ORR/OER bifunctional electrocatalysts for zinc–air batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…However, studies showed that metal selenides possess low electron conductivity and stability in energy-based applications. [19][20][21] Based on the above context, carbon nanofillers including graphene oxide, [22,23,24] carbon frameworks, [25] and carbon nanofibers [26] can be used to increase the electron conductivity of metal selenides. The highest electron conductivity and largest surface area of all carbon conductive fillers were found in graphene sheets, which also prevents the accumulation of metal selenides.…”
mentioning
confidence: 99%
“…However, studies showed that metal selenides possess low electron conductivity and stability in energy-based applications. [19][20][21] Based on the above context, carbon nanofillers including graphene oxide, [22,23,24] carbon frameworks, [25] and carbon nanofibers [26] can be used to increase the electron conductivity of metal selenides. The highest electron conductivity and largest surface area of all carbon conductive fillers were found in graphene sheets, which also prevents the accumulation of metal selenides.…”
mentioning
confidence: 99%
“…The 2D nanosheets of Ni 0.85 Se are made up of hexagonal structures, as seen in Figure S14a, which is well corroborated to FESEM analysis. The HRTEM image in Figure S14b represents the d spacing of 0.26 nm, which is well indexed with the (101) plane of the Ni 0.85 Se lattice . The crystalline nature of pristine Ni 0.85 Se is confirmed through SAED analysis in Figure S14c; the bright spots are clearly visible due to the crystallinity and lattice planes of the Ni 0.85 Se.…”
Section: Results and Discussionmentioning
confidence: 80%
“…The HRTEM image in Figure S14b represents the d spacing of 0.26 nm, which is well indexed with the (101) plane of the Ni 0.85 Se lattice. 52 The crystalline nature of pristine Ni 0.85 Se is confirmed through SAED analysis in Figure S14c; the bright spots are clearly visible due to the crystallinity and lattice planes of the Ni 0.85 Se. Introduction of the Ce dopant reduces the thickness of 2D nanosheets of Ni 0.85 Se, as shown in Figure 4a,b, which is well corroborated with FESEM.…”
Section: Mechanism Ofmentioning
confidence: 80%
“…22,23 As a result, various transition metal-based catalysts viz. selenides, 24,25 suldes, 26,27 borides, 28,29 nitrides, 30,31 phosphides, 32,33 and oxides 34 have been explored in the past. Despite signicant progress, most of these catalysts showed favorable activity for one particular reaction, but when used as a bifunctional or trifunctional catalyst, they failed to achieve an equivalent activity to advanced noble-metal catalysts.…”
Section: Introductionmentioning
confidence: 99%